2002
DOI: 10.3354/meps236205
|View full text |Cite
|
Sign up to set email alerts
|

Larval distribution of offshore spawning flatfish in the Gulf of Alaska: potential transport pathways and enhanced onshore transport during ENSO events

Abstract: Offshore and deepwater spawning flatfish species in the Gulf of Alaska, such as arrowtooth flounder Atheresthes stomias and Pacific halibut Hippoglossus stenolepis, have juvenile nurseries that are inshore, in bays or at the mouths of bays. Larvae must emigrate from their spawning areas along the continental slope and outer shelf towards shore, in a direction across the prevailing Alaskan Stream. Using a 20 yr time series of data from ichthyoplankton surveys in the Gulf of Alaska, we examine patterns of variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…We propose that the depth of the apex of the spawning rise is a means for the female to vertically position the eggs and the subsequent drifting larvae in the water column. Correct depth selection for egg release may ensure onshore transport into coastal juvenile nursery grounds by the prevailing current (Bailey & Picquelle 2002). Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that the depth of the apex of the spawning rise is a means for the female to vertically position the eggs and the subsequent drifting larvae in the water column. Correct depth selection for egg release may ensure onshore transport into coastal juvenile nursery grounds by the prevailing current (Bailey & Picquelle 2002). Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that population structure of benthic marine fishes is influenced by larval transport dependent on oceanic current systems and wind patterns (Parker 1989;Koutsikopoulos et al 1991;Nielsen et al 1998;Stepien 1999;Bailey and Picquelle 2002;Wilderbuer et al 2002;Knutsen et al 2007). Benthic species can experience genetic homogenization as a consequence of mixing during the transport of pelagic eggs and larvae despite geographically distinct spawning locations (Hauser et al 2006;Rooper et al 2006;Bailey et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Adult H. stenolepis are highly migratory, with some individuals moving hundreds of km over several months (Seitz et al ., ; Webster et al ., ). In addition, H. stenolepis have a long pelagic larval phase in the order of 6 months (St Pierre, ), in which they are dispersed by ocean currents that could result in long‐distance connectivity among populations (Thompson & Van Cleve, ; Skud, ; Bailey & Picquelle, ). Despite the plethora of evidence supporting extensive movement of H. stenolepis , little is known about gene flow among populations.…”
Section: Introductionmentioning
confidence: 99%